Measuring the impact of spin-triplet exciton orientation on photocurrent in an organic transistor. Issue 35 (30th June 2021) - Bittle, Emily G.; Engmann, Sebastian; Thorley, Karl; Anthony, John
Abstract : Angle dependent magneto-photocurrent in organic single crystal transistors reveals the anisotropy of triplets, verified by a spin-Hamiltonian model with zero-field splitting, providing a basis for metrics of singlet fission–triplet fusion devices. Abstract : The dynamics of triplet and singlet exciton populations in organic semiconductors offer interesting possibilities in improving optical device efficiency, while also attracting interest for future applications as manipulable states for quantum-state based computing. For technological applications, transduction of the exciton state is essential, thus detailed information on how the exciton dynamics affect device outputs is required. In this study, we measure the magnetic field response of the photocurrent in organic transistors to investigate the electrical signal resulting from singlet–triplet exciton dynamics. We find that controlling the orientation of the magnetic dipole orientation of the triplet by varying both the magnitude and orientation of the magnetic field with respect to single crystal axes in anti -2, 8-difluoro-5, 11-bis(triethylsilylethynyl)anthradithiophene ( a diF TES ADT) allows us to manipulate the amount of current detected as a result of singlet fission.